Quality of service for packet telephony over mobile ad hoc networks. - Giacomazzi, P. (IEEE Network : the magazine of global information exchange)
IP telephony over mobile ad hoc networks is a topic of emerging interest in the research arena as one of the paths toward the fixed-mobile convergence in telecommunications networks. To investigate the performance characteristics of this service, we propose a complete system architecture, which includes a MAC protocol, a routing protocol, and the treatment of voice packets. The telephone system is analyzed in the case of point-to-point calls inside the ad hoc network, and the end-to-end performance is assessed in terms of the percentage of blocked and dropped calls, packet loss and packet delay. The analysis takes into account network scalability by investigating how; the size of the multihop ad hoc network impacts the quality of service. Moreover, the synthetic mean opinion score of the telephone service is evaluated according to the ITU-T E-model